KRITIK KONSEP POLITIK MACHIAVELLI DALAM PERSPEKTIF ETIKA POLITIK ISLAM (PERBANDINGAN DENGAN TEORI ETIKA POLITIK AL MAWARDI) - Zein, Fuad Muhammad (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2016)
Basically, politics is a human need. As social beings, humans need to regulate political life. In order to be run in accordance with a common goal, the ethics and morals is a necessity that must be juxtaposed in politics. However, Machiavelli sense of ethics basing on two things, namely the Ancient Western ethics and Catholic ethics. He is holding on Western ethics derived from the Ancient Romans, whice based on the thinking that to retain power strength of spirit to fight to be the underdog. He stated that the Catholic ethics only make men weak because only orients his life on things that smelled hereafter. This thought does not give real contribution in political battles and power. As for foreign policy, Machiavelli emphasizes the shrewdness prince in terms of diplomacy. He stated that a prince in diplomacy must wear deception lion and the fox (deer). The difference between Machiavelli's political ethics is in stark contrast to what was formulated by al Mawardi. The difference is based on the basic beliefs between the two is also berbeda.Machiavelli leaned that ethics is not required in power when the condition of the people is unethical, because it was thought worth sia.Berbeda with al Mawardi, who rely on the Qur'an and Sunnah regardless of the conditions masyarakat. He always insisted that every ruler has always adhered to the ethical and moral values ​​that have been described in the Qur'an and as Sunnah. if thus, it can be concluded that, in truth Machiavelli does not provide solutions to community conditions and the improved of politis. Cause stability also what he says violates human nature when it agreed in shaping society, so that he saw the man was an enemy to the other man